2019
DOI: 10.1007/s00424-019-02287-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with C-type natriuretic peptide impacts differently in the aorta of normotensive and hypertensive rats

Abstract: The aim of this study was to determine whether exogenous administration of C-type natriuretic peptide (CNP) induces functional and morphological vascular changes in spontaneously hypertensive rats (SHR) compared with normotensive rats. Male 12week-old normotensive Wistar and SHR were administered with saline (NaCl 0.9%) or CNP (0.75 μg/h/100 g) for 14 days (subcutaneous micro-osmotic pumps). Systolic blood pressure (SBP) was measured in awake animals and renal parameters were evaluated. After decapitation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Corresponding to individuals with essential hypertension, SHRs display increased expression of proinflammatory cytokines in both the heart and the vasculature. 3 , 4 Chronic treatment with CNP in SHRs has been shown to decrease left ventricular expression of interleukin-1β, interleukin-6, and TNF-α3, supporting previous findings in aortas of SHRs. 4 In an earlier study, Moyes et al 6 compared wild-type mice with endothelial cell–specific CNP-knockout mice, in which increased levels of leukocyte rolling on vascular beds together with neutrophils and macrophage accumulation in extravascular tissues following TNF-α administration were observed.…”
Section: Cnp Is Anti-inflammatory and Reverses Oxidative Stresssupporting
confidence: 82%
See 1 more Smart Citation
“…Corresponding to individuals with essential hypertension, SHRs display increased expression of proinflammatory cytokines in both the heart and the vasculature. 3 , 4 Chronic treatment with CNP in SHRs has been shown to decrease left ventricular expression of interleukin-1β, interleukin-6, and TNF-α3, supporting previous findings in aortas of SHRs. 4 In an earlier study, Moyes et al 6 compared wild-type mice with endothelial cell–specific CNP-knockout mice, in which increased levels of leukocyte rolling on vascular beds together with neutrophils and macrophage accumulation in extravascular tissues following TNF-α administration were observed.…”
Section: Cnp Is Anti-inflammatory and Reverses Oxidative Stresssupporting
confidence: 82%
“…Also, the results suggest that long-term administration of CNP has potential in long-term treatment of hypertension, whereas short-term CNP administration may be less relevant. A possible explanation is that the acute vasodilatory response, especially in larger vessels, greatly relies on the nitric oxide system, which seems impaired in spontaneously hypertensive rats (SHRs), 3 , 4 and interaction between CNP and the nitric oxide system remains controversial. Furthermore, CNP administration in mice does not affect renal function, 2 whereas ANP or BNP can induce worsening of renal failure because of excessive vasodilation and hypotension.…”
Section: Cnp Reduces Peripheral Vascular Resistancementioning
confidence: 99%
“…Of all the short stature skeletal dysplasias, however, achondroplasia and hypochondroplasia offer the most plausible biologic explanation for high hypertension prevalence based on our current understanding of elevated CNP levels in these patients (Olney et al, 2015) and the observation in average stature individuals that more vascular disease risk factors are highly correlated with elevated CNP levels in blood (Prickett et al, 2013). Though CNP has been shown to cause vasodilation in hypertensive mouse models (Caniffi et al, 2019), it is likely that the elevated CNP present in patients with achondroplasia cannot be effectively bound by its paired receptor, NPR-B. The intracellular signaling, which is activated by mutated FGFR3 in patients with achondroplasia, not only inhibits chondrocyte proliferation, but also inhibits the function of NPR-B.…”
Section: Discussionmentioning
confidence: 99%
“…Moyes et al [ 96 ] found that administration of small-molecule NPR-C agonists promoted vasorelaxation of isolated resistance arteries and reduced blood pressure in WT animals. Treatment with CNP effectively attenuated vascular remodeling and reduced systolic blood pressure in hypertensive rats and decreased both proinflammatory and profibrotic cytokines [ 101 ]. In addition, CNP activated the vascular NO system and exerted an antioxidant effect in the aortic tissue of both hypertensive rats and normotensive rats [ 101 ].…”
Section: Vasoactive Peptides and Vascular Aging-related Diseasesmentioning
confidence: 99%
“…Treatment with CNP effectively attenuated vascular remodeling and reduced systolic blood pressure in hypertensive rats and decreased both proinflammatory and profibrotic cytokines [ 101 ]. In addition, CNP activated the vascular NO system and exerted an antioxidant effect in the aortic tissue of both hypertensive rats and normotensive rats [ 101 ]. Impaired local endogenous CNP may be associated with increased vascular calcium deposition in rat aortas with vascular calcification [ 102 ].…”
Section: Vasoactive Peptides and Vascular Aging-related Diseasesmentioning
confidence: 99%